2021
DOI: 10.1186/s12284-021-00477-w
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Pyramiding of QTLs for Rice Grain Size Based on Short-Wide Grain CSSL-Z563 and Fine-Mapping of qGL3–2

Abstract: Background Chromosome segment substitution lines (CSSLs) can be used to dissect complex traits, from which single-segment substitution lines (SSSLs) containing a target quantitative trait loci (QTL) can be developed, and they are thus important for functional analysis and molecular breeding. Results A rice line with short wide grains, CSSL-Z563, was isolated from advanced-generation backcross population (BC3F6) derived from ‘Xihui 18’ (the recipien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 31 publications
0
27
1
Order By: Relevance
“…Zhang et al (2020) showed that pyramid of qGL5 (a=0.30) and qGL6 (a=0.13) produced longer grains (G=0.74) of D2 than S2 and S3 at the genetic backgrounds of Nipponbare. Liang et al (2021) argued that pyramiding of different QTLs produces different epistatic interaction and their performance after pyramiding depends on the comparison between the algebraic sum of additive and epistatic effects of QTLs in the pyramidal line and the additive effect of all single QTLs. On the basis of the rule, so long as knowing the additive effects and epistatic effects of target QTLs at the speci c environment, the phenotype of novel pyramided genotypes at speci c environment can be predicted and then suitable genotypes can be selected according to our breeding goal, thus realizing the concept of design breeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al (2020) showed that pyramid of qGL5 (a=0.30) and qGL6 (a=0.13) produced longer grains (G=0.74) of D2 than S2 and S3 at the genetic backgrounds of Nipponbare. Liang et al (2021) argued that pyramiding of different QTLs produces different epistatic interaction and their performance after pyramiding depends on the comparison between the algebraic sum of additive and epistatic effects of QTLs in the pyramidal line and the additive effect of all single QTLs. On the basis of the rule, so long as knowing the additive effects and epistatic effects of target QTLs at the speci c environment, the phenotype of novel pyramided genotypes at speci c environment can be predicted and then suitable genotypes can be selected according to our breeding goal, thus realizing the concept of design breeding.…”
Section: Discussionmentioning
confidence: 99%
“…D2 harbored both qGL3, qGL11 and qCD3 and displayed shorter grain and lower chalkiness degree. Lower chalkiness degree is one of very important factors affected rice grain quality (Yang et al 2021) and different grain size are import to meet the requirement of various people's preferences (Feng et al 2021;Liang et al 2021). Thus, some secondary substitution lines with signi cantly lower chalkiness degree than Xihui 18, such as S1 and D1 are potential to be directly used as novel rice restorer lines to match with sterile lines.…”
Section: Discussionmentioning
confidence: 99%
“…Lower chalkiness degree is a very important factor affecting rice grain quality (Yang et al 2021). Again, different grain sizes are import to meet the requirement of various people's preferences (Feng et al 2021;Liang et al 2021). Thus, these four SSSLs are potential to be directly used as novel rice restorer lines to breed novel hybrid rice varieties.…”
Section: Discussionmentioning
confidence: 99%
“…We also took the half of the difference of phenotype value into account as caused by inheritance. Thus, the epistatic effects between non-allele QTLs were estimated as half of the mean phenotypic values of (Xihui18+DSSL ij )-(SSSL i +SSSL j ) (Liang et al 2021). Finally, we used IBM SPSS Statistics 25.0 to conduct multiple comparison for all SSSLs and DSSLs as well as Xihui18.…”
Section: Epistatic Interaction Analysis Between Target Qtls By Dsslsmentioning
confidence: 99%
See 1 more Smart Citation